A composite metamaterial with sign switchable elastic and hygrothermal properties induced by stress direction and environmental change reversals. (15th July 2019) - Lim, Teik-Cheng
Abstract: The negativity of material properties has opened up the possibility for the design of materials and structures that can perform in ways that are not achievable by conventional ones. Yet, conventional materials still possess their merits in certain applications. This paper explores a class of triangular-based composite metamaterial microstructure, with pin joints, that exhibits positive and negative Poisson's ratio as a result of tensile and compressive loads respectively. By incorporating an additional set of rods, the modified microstructure behaves as a positive hygrothermal expansion material due to decrease in temperature and/or moisture concentration, but exhibits negative hygrothermal expansivity upon the increase of temperature and/or moisture concentration. The possibility of producing materials with behavioral multiplicity offers opportunities for development of materials and structures that reverse their behavior depending on the switch in stress sign as well as a switch in the sign for change(s) to the environmental temperature and/or moisture concentration.